EVALUASI PROGRAM PENGENTASAN KEMISKINAN (Studi Kasus Pemberdayaan Ekonomi pada Program Nasional Pemberdayaan Masyarakat (PNPM) Mandiri Perkotaan di Kelurahan Perwira Kecamatan Bekasi Utara Kota Bekasi Jawa Barat) - Ari Saptono (Jurnal Ilmiah Econosains, 2013)
ABSTRACTThis research is to evaluate the process of economy empowerment on PNPM Mandiri Perkotaan in Officer North Bekasi with targeted research that examines the implementation of economic development programs related to community participation, community capacity building, as well as assessing the degree of empowerment community. Model of evaluation which is used in this research is CIPP evaluation. In general, this evaluation model consists of four evaluation objectives, namely: Context Evaluation, Input Evaluation, Process Evaluation, Product evaluation. Research results showed: there is no standard criteria or indicators to determine the receivers of loan; achievement rate in providing infrastructure BKM is 42.85%, it’s in moderate category; staffing is in accordance with the procedures set out in the guidelines; public institutions is fully established. People's understanding of revolving loans varies. Public participation has achieve minimum target of 40%. The quantity of training which can improve skill must be increased since skills owned by the members are expected can increase family income through home businesses. Perwira District has not develop partnership yet with external party such as: bank,corporate, and higher education institution. This economy empowerment program has satisfactory result, indicated by: 93% of repayment rate, 2,63% of loans at risk , 211,36% cost coverage ratio, and 6,54% return on investment.Keywords: evaluate, economy, empowerment, PNPM